2022
DOI: 10.1117/1.jmi.9.3.033503
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a method for tumor growth simulation in virtual clinical trials of breast cancer screening

Abstract: . Purpose Image-based analysis of breast tumor growth rate may optimize breast cancer screening and diagnosis by suggesting optimal screening intervals and guide the clinical discussion regarding personalized screening based on tumor aggressiveness. Simulation-based virtual clinical trials (VCTs) can be used to evaluate and optimize medical imaging systems and design clinical trials. This study aimed to simulate tumor growth over multiple screening rounds. Approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…10,11 More general lesions can be used in multiple anatomical locations with minor modifications. Computational lesion models intended for simulated medical imaging 3,4,[12][13][14][15] use data from clinically imaged lesions as the basis for tuning model parameters; however, this immediately suggests an inconsistency with the representation of image-based computational lesions compared to images of real lesions. Lesions differing in high-frequency content-differences between spiculated margins, for example-can be rendered null by the imaging process.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 More general lesions can be used in multiple anatomical locations with minor modifications. Computational lesion models intended for simulated medical imaging 3,4,[12][13][14][15] use data from clinically imaged lesions as the basis for tuning model parameters; however, this immediately suggests an inconsistency with the representation of image-based computational lesions compared to images of real lesions. Lesions differing in high-frequency content-differences between spiculated margins, for example-can be rendered null by the imaging process.…”
Section: Introductionmentioning
confidence: 99%
“…Dustler et al reported 36% reduction in false positives, when MI was performed together with DM, in two separate acquisitions 6 . A multimodality approach of simultaneous DBT and mechanical imaging (MI) -DBTMI, developed at our institution [8][9][10] , has potential to increase both sensitivity and specificity, without extending the clinical workflow.…”
Section: Introductionmentioning
confidence: 99%